MODEL MATEMATIS SEDERHANA UNTUK PERKIRAAN JANGKAUAN PENGUKURAN PADA DETEKTOR GEIGER MULLER - Benar Bukit; Jos Budi Sulistyo; Abdul Jalil (BATAN, 2012)
A SIMPLE MATHEMATICAL MODEL FOR THE ESTIMATION OF THE MEASUREMENT RANGE ON GEIGER-MULLER DETECTORS. Proposed here is a simple mathematical model which allows the use of information on dead time and sensitivity of a Geiger Muller (GM) detector for back-ofthe-evenlope estimation of resolution,dose rate measurement range, and thedose rate measurement error as a function of incident dose rate. The aforemention model was then employed for comparing the measurementrange and resolution of 34 types of GM detectors manufactured by LND,Inc. It was found that they generally did not attain the widest Measurement range and the finest resolution at the same time. Futher, itwas found that among the 34 detector types analyzed, the 7802 possessed the finest measurement resolution while the 71623 possessedthe widest measurement range.Keyword : GM detector, mathematical model, measurement rangeMODEL MATEMATIS SEDERHANA UNTUK PERKIRAAN JANGKAUAN PENGUKURAN PADA DETEKTOR GEIGER-MULLER. Suatu model matematis sederhana untuk menggunakan informasi mengenai waktu mati (dead time) dan sensivitas suatu detektor Geiger Muller (GM) untuk mendapatkan perkiraan kasar secara cepat atas resolusi, jangkauan pengukuran yang timbul pada saat laju dosis yang sebenarnya bernilai tertentu. Model matematis tersebut kemudian digunakan untuk membandingkan jangkauan pengukuran dan resolusi 34 jenis detektor GM yang dibuat oleh LND, Inc. Ditemukan bahwa detektor-detektor GM tersebut secara umum tidak sekaligus mencapai jangkauan ukur dan resolusi tertinggi. Diantara 34 jenis detektor GM tersebut, jenis 7802 memiliki resolusi yang tertinggi, sedangkan 71623 memiliki jangkauan ukur terbesar.Kata kunci: detektor GM, model matematis, jangkauan pengukuran